Bending response of FG plates resting on elastic foundations in hygrothermal environment with porosities. (1st April 2019) - Zenkour, A.M.; Radwan, A.F.
Abstract: This work is devoted to investigate the effects of moisture and temperature on the bending analysis of functionally graded porous plates resting on two parameters elastic foundation. The effects of transverse normal and shear strains are taken into account. The governing equations are determined via the principle of virtual work. Analytically Navier's method is utilized to solve the governing equations for simply-supported FG porous plate. The determined results are verified by comparing the results obtained for the FG non-porous and porous plates with the available ones in the literature. The effects due to exponent graded and porosity factors, moisture and thermal loads, foundation stiffnesses, aspect ratio and side-to-thickness ratio on FG porous plate are all investigated.